The power of a touch: Regular touchscreen training but not its termination affects hormones and behavior in mice - Quante, Sophia Marie; Siewert, Viktoria; Palme, Rupert; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene (Frontiers in Behavioral Neuroscience, 2023)
Touchscreen-based procedures are increasingly used in experimental animal research. They not only represent a promising approach for translational research, but have also been highlighted as a powerful tool to reduce potential experimenter effects in animal studies. However, to prepare the animals for a touchscreen-based test, an often time-consuming training phase is required that has itself been shown to cause increased adrenocortical activity and anxiety-like behaviour in mice. While these findings point at a potentially negative effect of touchscreen training at first glance, results have also been discussed in light of an enriching effect of touchscreen training. The aim of the present study was therefore to shed more light on recently reported touchscreen training effects, with a particular focus on the termination of the training routine. Specifically, we investigated whether the termination of regular touchscreen training could constitute a loss of enrichment for mice. Thus, we assessed faecal corticosterone metabolites (FCMs), exploratory-, anxiety-like and home cage behaviour in touchscreen-trained mice in comparison to food restricted and ad libitum fed mice, as a restricted diet is an integral part of the training process. Furthermore, we compared these parameters between mice that were continuously trained and mice whose training was terminated two weeks earlier. Our results confirm previous findings showing that a mild food restriction increases the animals’ exploratory behaviour and shifts their activity rhythm. Moreover, touchscreen training was found to increase FCM levels and anxiety-like behaviour of the mice. However, no effect of the termination of touchscreen training could be detected, a finding which contradicts the enrichment loss hypothesis. Therefore, we discuss two alternative explanations for the findings. Yet, the current state of knowledge is not sufficient to draw final conclusions at this stage. In compliance with the refinement endeavours for laboratory animals, further research should assess the severity of touchscreen procedures to ensure a responsible and well-founded use of animals for experimental purposes.